Effect of Motivation and Compensation on Performance of Jember Regency Paddy Farmer through Job Statisfaction as Intervening Variable - Prayuginingsih, Henik; Fauzi, Nurul Fathiyah; Nandaka, Arrifaldo Dwi; Nugroho, Johan Wahyu (Universitas Muhammadiyah Jember, 2024)
Farmer strengthening is needed to make farmer stand on their proffession for supporting food security program. Aimed of this study was, want to know the effect of motivation and compensation on performance of Jember Regency paddy farmer through job statistfaction as intervening variable. Study was done at Jember Regency as the fourth big rice producer in East Java in January 2022 as rainy cultivation season. Sample was 80 farmers consist of 20 farmers form each four Sub District represent four region in Jember. They were Kalisat (north), Ledokombo (east), Ajung (south) and Tanggul (west) choosen because has widest rice filed. Motivation and job statisfaction was measured by Likert scale, beside compensation was mesured by income from paddy farming and performance was measured by land productivity. Data was analized by path analysis. The result were: (1) motivation, compensation and job statisfaction affected 57.30% performance of farmer simultaneously and significant at 1% level meanwhile 42.70% the rest was caused by another factors; (2). motivation and compensatian simultanuosly affected only 9.6% on job statisfaction but significant at 1% test level meanwhile 90.40 % the rest was caused by another factors; (3) motivation affected 1.06 % directly and 0.16% indirectly through job statisfaction on performance of paddy farmer at Jember Regency; (4) compensation affected 53.44% directly and 0.01% indirectly through job statisfaction on performance of paddy farmerat Jember Regency.